A Solution‐Processed Ultrafast Optical Switch Based on a Nanostructured Epsilon‐Near‐Zero Medium. Issue 27 (3rd May 2017) - Guo, Qiangbing; Cui, Yudong; Yao, Yunhua; Ye, Yuting; Yang, Yue; Liu, Xueming; Zhang, Shian; Liu, Xiaofeng; Qiu, Jianrong; Hosono, Hideo
Abstract : All the optical properties of materials are derived from dielectric function. In spectral region where the dielectric permittivity approaches zero, known as epsilon‐near‐zero (ENZ) region, the propagating light within the material attains a very high phase velocity, and meanwhile the material exhibits strong optical nonlinearity. The interplay between the linear and nonlinear optical response in these materials thus offers unprecedented pathways for all‐optical control and device design. Here the authors demonstrate ultrafast all‐optical modulation based on a typical ENZ material of indium tin oxide (ITO) nanocrystals (NCs), accessed by a wet‐chemistry route. In the ENZ region, the authors find that the optical response in these ITO NCs is associated with a strong nonlinear character, exhibiting sub‐picosecond response time (corresponding to frequencies over 2 THz) and modulation depth up to ≈160%. This large optical nonlinearity benefits from the highly confined geometry in addition to the ENZ enhancement effect of the ITO NCs. Based on these ENZ NCs, the authors successfully demonstrate a fiber optical switch that allows switching of continuous laser wave into femtosecond laser pulses. Combined with facile processibility and tunable optical properties, these solution‐processed ENZ NCs may offer a scalable and printable material solution for dynamic photonic and optoelectronic devices. Abstract : A novel ultrafast optical switch enabled by an epsilon‐near‐zero (ENZ) medium of colloidal indium tin oxide nanocrystals is demonstrated, which is based on its strong ultrafast nonlinear optical characters (with >2 THz response speed and ≈160% modulation depth) benefitting from the highly confined geometry in addition to the ENZ enhancement effect of the nanostructured ENZ medium.